The Iliviaq Returns to Gjoa Haven: Interrogating Objects from Roald Amundsen’s Collection in the Nattilik Heritage Centre - Wang, Tone (Études Inuit Studies, 2018)
Museum collaboration and object return has been discussed and examined widely in practice and literature in recent decades (e.g. Fienup-Riordan 1998; Peers and Brown 2003; Basu 2017). This paper examines an instance of object return, a wooden bowl. The bowl was part of the Roald Amundsen/Gjoa Haven Collection held at the Museum of Cultural History in Oslo, Norway, and returned to the Nattilik Heritage Centre in Gjoa Haven in 2013. Upon its return to Gjoa Haven, the bowl became the focus of interrogations and discussions to determine how it might be related to local heritage and traditional knowledge. This paper explores how this particular instance of memory work might contribute to our understanding of the processes at play in repatriation activities, or, to quote Paul Basu, the bowl’s “entanglements of ongoing social, spatial, temporal and material trajectories and relationships, dislocations and relocations” (2017, 2) as seen from the perspective of Gjoa Haven residents.